Administration of Security Deposits in Residential Properties in Developing Countries: Evidence from Nigeria - Aguome, N. M.; Emoh, F. I.; Ewurum, N. I.; Ifeanacho, K. P.; Ezema, C. C.; Ani, I. E. (International Journal of Real Estate, 2026)
Security deposit (SD) is one of the most debated financial transactions between property owners/managers and tenants. This research quantitatively examined the administration of security deposit on residential properties in Nigeria with a view to enhancing its implementation and administration. Primary data was retrieved from 280 firms of estate surveyors and valuers in Nigeria via a structured questionnaire. The retrieved data was analysed using descriptive statistics. The study found that there is arbitrariness in the implementation and administration of SD on residential properties in Nigeria. There is arbitrary inclusion of SD clauses in the tenancy/lease agreement. Type of tenant/history of tenant, property finishings, and type of building are factors that determine the sum of money to charged as SD. The challenges associated with the administration of SD include devaluation of SD money due to inflation, noncompliance of the SD refund clause in the tenancy agreement by landlords, strain in the relationship between firms and tenants due to the refund of SD, amongst others. The study recommended that a law should be enacted at either the state or national level that would regulate the implementation and administration of SD, as this would reduce the arbitrariness, discrepancies, and conflicts prevalent in the administration of SD.